Scattering by inductive post in uniformly curved rectangular - Petrusenko, IV; Chumachenko, VP (Iee-Inst Elec Eng, 2003)
A rigorous solution to the problem of wave scattering by a single inductive post in a continuously curved rectangular waveguide is presented. The position of the post and its radius are arbitrary. The waveguide curvature can be varied over wide limits. An efficient mathematical model of the unit is based on the domain-product technique. The theory developed is applied to the normalised reactances of the discontinuity and the induced surface current. The results obtained lend support to the validity of the known approximate solution for a thin post as far as this approximation goes. It is found that data for a centrally placed post deviate slightly from-those for a straight guide in a broad interval of curvature variation. The off-centre shift affects the characteristics appreciably. Over full waveguide bandwidth, the paper provides the data that are essential in the design of devices containing uniform bends, such as bandpass filters or transmission resonators.
Keywords: Wave-Guide Junctions; H-Plane; Boundary Elements; Waveguide; Discontinuities; Obstacle